Travel notes from the new literacy studies : instances of practice - Pahl, Kate; Rowsell, Jennifer, 1969- (New perspectives on language and education., 2006)
Joining two important fields, that of literacy and multimodality, with a focus on local and global literacies, this book includes chapters, work on media; popular culture and literacy; weblogs, global and local crossings; in and out of educational settings in such locations as the US, the UK, South Africa, Australia and Canada.